2022
DOI: 10.2166/wpt.2022.019
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of natural coagulant extraction from walnut seeds for water turbidity removal

Abstract: In this study, natural coagulant obtained from walnut seeds was used in water treatment for the removal of turbidity as a coagulant and as a coagulant aid with alum. The study was conducted by using a jar test under various operational parameters. The tests were carried out with initial turbidity of 10–200 NTU, pH of 3–11, and natural coagulant dose of 1–5 ml/L. The characterization of walnut natural coagulant was carried out using SEM, FTIR, EDX, and zeta potential analyzer. The coagulation activity and turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…This was done using a magnetic stirrer. Then the solution was filtered using a filter paper [ 32 ]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This was done using a magnetic stirrer. Then the solution was filtered using a filter paper [ 32 ]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, physicochemical methods have shown the ability to remove various suspended and floating matter, while sedimentation has been used for primary water clarification (Pokhrel and Viraraghavan, 2004;Kamali and Khodaparast, 2015;Hubbe et al, 2016;Toczyłowska-Mamińska, 2017). Besides synthetic materials, various cost-effective natural adsorbents such as agricultural and forest residues have also been utilized as bio-absorbents for treatment purposes (Janoš et al, 2009;Zedan et al, 2022). It has suggested that the ash raw bagasse (Valix et al, 2004), plant stem (Bazrafshan and Kord Mostafapour, 2013), cellulose-based waste (Annadurai et al, 2002), red pine chips (Ozkan et al, 2023) have some of the natural absorbent that effective for removing various type of coloring matters from wastewater.…”
Section: Introductionmentioning
confidence: 99%